Pengaruh Sikap pada Pelajaran Matematika dan Kebiasaan Belajar Matematika ditinjau dari Gaya Belajar terhadap Prestasi Belajar Matematika Siswa Kelas VIII SLTP Berorientasi Islam di Makassar - Ilham Minggi; Muhammad Dinar; Hasnainah (Issues in Mathematics Education (IMED), 2020)
This research was conducted to determine the effect of attitudes on mathematics and mathematics learning habits in terms of learning style to Mathematics Learning Achievement Grade VIII SLTP Islamic oriented in Makassar. The technique of collecting data using instrument questionnaire of attitudes on mathematics, questionnaire of mathematics learning habits, questionnaire of learning style, and test result of mathematics learning. The result of the research shows that: (1) of 80 respondents, there were 27 students with visual learning style, 14 students with auditory learning style, and 39 students with kinesthetic learning style. (2) attitudes on mathematics and mathematics learning habits are in the high category for visual and kinesthetic learning style, and low category for auditory learning style, (3) mathematics learning achievement in the medium category for each learning style group, (4) attitudes on mathematics and mathematics learning habits jointly influence mathematics learning achievement for each learning style group, (5) attitudes on mathematics directly effect on mathematics learning achievement for visual and kinesthetic learning style group, (6) mathematics learning habits directly effect on mathematics learning achievement for visual learning style group, (7) attitudes on mathematics indirectly effect on mathematics learning achievement through variable mathematics learning habits for visual learning style group.